Evaluasi Ergonomi Visual: Dampak Penggunaan Dark Mode terhadap Kelelahan Mata (Eye Strain) pada Mahasiswa - Alhafiz Okliano Hardianta; M.Radit Qoiri Hasibuan; M. Wira Adithya; Muhammad Rafly Solihin; M. Khalil Gibran (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
The long time students spend using devices on campus makes them more likely to develop Computer Vision Syndrome (CVS). To help lessen eye strain from looking at bright screens, many people are now using the Dark Mode feature. This study was done to check how well the interface helps reduce eye strain in university students by looking at its visual ergonomics. This study used a descriptive quantitative method by giving out a questionnaire with a 1 to 5 scale, and it included 36 students who use their devices for more than five hours each day. The analysis shows that the general level of visual fatigue is moderate, with an average score of 2.43. The main issues users are facing are blurry vision with a score of 2.58 and headaches starting up with a score of 2.50. On the other hand, the indicators for dry eyes and difficulty focusing both had lower scores of 2.30, which puts them in the Low category. In short, Dark Mode works well at reducing glare and helping keep the eyes moist, but it hasn't completely fixed the eye muscle strain that comes from using screens for a long time. So, it's still important to adjust the screen brightness in a balanced way to get the best possible comfort for your eyes.